Surveillance, responsibility and control: an analysis of government and industry discourses about "problem" and "responsible" gambling. (3rd March 2016) - Miller, Helen E.; Thomas, Samantha L.; Smith, Kylie M.; Robinson, Priscilla
Abstract: Background : Discussions of gambling have traditionally focused on ideas of "problem" and "responsible" gambling. However, few studies have examined how Institutions attempt to exert social control over gamblers in order to promote so-called "responsible" behaviour. In this study, we examine the way "problem" and "responsible" gambling are discussed by Australian governments and the gambling industry, using a theoretical framework based on the work of Foucault. Method : We conducted a thematic analysis of discourses surrounding problem and responsible gambling in government and gambling industry websites, television campaigns and responsible gambling materials. Results : Documents distinguished between gambling, which was positive for the community, and problem gambling, which was portrayed as harmful and requiring medical intervention. The need for responsible gambling was emphasised in many of the documents, and reinforced by mechanisms including self-monitoring, self-control and surveillance of gamblers. Conclusions : Government and industry expect gamblers to behave "responsibly", and are heavily influenced by neoliberal ideas of rational, controlled subjects in their conceptualisation of what constitutes "responsible behaviour". As a consequence, problem gamblers become constructed as a deviant group. This may have significant consequences for problem gamblers, such as the creation of stigma.